Giant and flexible toroidal circular dichroism from planar chiral metasurface - Shijie Kang; Haitao Li; Jiayu Fan; Jiusi Yu; Boyang Qu; Peng Chen; Xiaoxiao Wu (APL Materials)
Chirality, a fundamental concept describing an object cannot superpose with its mirror image, is crucial in optics and photonics and leads to various exotic phenomena, such as circular dichroism and optical activity. Recent findings reveal that besides electric and magnetic dipoles, toroidal dipoles, an elusive part of dynamic multipoles, can also significantly contribute to chirality. However, as toroidal dipoles are typically represented by solenoidal currents circulating on a three-dimensional (3D) torus, toroidal circular dichroism is usually observed in 3D intricate microstructures. Facing corresponding challenges in fabrication, integration, and application, it is generally difficult to employ toroidal circular dichroism in compact metasurfaces for flexible modulation of chiral interactions between electromagnetic waves and matter. To overcome these stringent challenges, we propose and experimentally demonstrate the giant toroidal circular dichroism in a bilayer metasurface that is comprised of only planar layers, effectively bypassing various restrictions imposed by 3D microstructures. With the introduction of a displacement, or bilayer offset, between the opposite layers, we experimentally achieve giant chiral responses with the intrinsic circular dichroism (CD) reaching 0.69 in measurements, and the CD can be quantitatively manipulated in a simple manner. The giant intrinsic chirality primarily originates from distinct excitations of in-plane toroidal dipole moments under circular polarized incidences, and the toroidal chiral response is quantitatively controlled by the bilayer offset. Therefore, our work provides a straightforward and versatile approach for the development of giant and flexible intrinsic chirality through toroidal dipoles with inherently planar layers, important for applications in communications, sensing, and chiroptical devices.